The Size Distribution of Firms, Cournot, and Optimal Taxation - Gersovitz, Mark (IMF Working Papers; Working Paper ;, 2006)
Tax laws and administrations often treat different size firms differently. There is, however, little research on the consequences. As modeled here, oligopolists with different efficiencies determine the size distribution of firms. A government that maximizes a weighted sum of consumer surplus, profits, and tax receipts can tax firms with different efficiencies differently and provides a reference point for other, more restricted differential tax systems. Taxes include a specific sales tax, an ad valorem sales tax, and a profits tax with imperfect deductibility of capital cost, and a combination of the last two. In general there is a pattern of tax rates by efficiency of firm. It is heavily dependent on the social valuation of tax receipts. Analytic and simulation results are provided. When both ad valorem taxes and the imperfect profits tax are combined, simulations suggest that the former rate is higher and the latter rate is lower for relatively inefficient firms.